Electrocatalyst as well as preparation method and application thereof

By growing fluorine-doped nickel-cobalt phosphides and electrodeposited cerium-ferrolayered double hydroxide compounds on the conductive substrate, forming a three-dimensional heterostructured electrocatalyst, the problem of low activity of non-precious metal-based oxygen evolution electrocatalysts in the prior art under high current density is solved, and efficient alkaline high-current oxygen evolution performance is achieved.

CN119640311AActive Publication Date: 2025-03-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311203426.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-18
Publication Date
2025-03-18
Estimated Expiration
2043-09-18

AI Technical Summary

Technical Problem

Existing non-precious metal-based oxygen evolution electrocatalysts exhibit low activity and poor performance at high current density, making it difficult to meet the needs of industrial production.

Method used

A three-dimensional heterostructure electrocatalyst formed by conductive substrate-supported fluorine-doped nickel-cobalt phosphide (F-NiCoP) and cerium-ferrolayered double hydroxide (CeFe-LDH) was prepared by in-situ growth and electrodeposition technology.

Benefits of technology

It achieves good catalytic activity and stability under high current density, significantly improves the performance of the electrocatalyst, and is suitable for alkaline high current oxygen analysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640311A_ABST
    Figure CN119640311A_ABST
Patent Text Reader

Abstract

The invention discloses an electrocatalyst and a preparation method and application thereof, and belongs to the field of electrocatalysts. The electrocatalyst comprises a conductive substrate and an active component, the active component is loaded on the surface of the conductive substrate; the structural formula of the active component is CeFe-LDH (at) F-NiCoP; the F-NiCoP is fluorine-doped nickel cobalt phosphide, and the CeFe-LDH is a cerium iron layered dihydroxide compound; f-NiCoP in the active component grows on the surface of the conductive substrate in situ in the form of a two-dimensional nanosheet array, and CeFe-LDH nanoparticles in the active component grow on the surfaces of F-NiCoP two-dimensional nanosheets to form a three-dimensional heterogeneous structure of the active component. The three-dimensional heterostructure electrocatalyst prepared by the method has rich catalytic active sites and excellent oxygen evolution catalytic activity, shows excellent durability under an alkaline large-current condition, and has great significance in promoting development of green and clean energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalysts, and in particular relates to an electrocatalyst and a preparation method and application thereof. Background Art

[0002] As a green energy source, hydrogen energy is considered to be an ideal substitute for traditional fossil fuels due to its high energy density, high conversion efficiency, abundant sources, and clean and pollution-free characteristics. Electrocatalytic hydrolysis is a very promising way to produce hydrogen. The hydrogen production process is clean and pollution-free, and large-scale hydrogen production can be achieved. Among them, the oxygen evolution reaction (OER) is an important half-reaction. Due to its complex reaction process and kinetic hysteresis, it determines the efficiency of the entire electrocatalytic hydrolysis process. At present, precious metal (Ir and Ru)-based catalysts have good oxygen evolution catalytic activity. However, due to the scarcity of precious metals on earth and their high cost, it is difficult to achieve large-scale production and application. Therefore, it is of great significance to develop non-precious metal-based oxygen evolution electrocatalysts with low cost and excellent performance.

[0003] Although a series of non-precious metal-based oxygen evolution electrocatalysts have been reported in recent years, most of them can only drive OER at a relatively low current density (≤250 mA cm-2), while industrial production often requires catalysts with a current density of 500 mA cm-2. -2 , even 1000mA cm -2 Therefore, the development and design of alkaline high current oxygen evolution electrocatalysts are of great significance to the development of water electrolysis hydrogen production technology.

[0004] At present, transition metal phosphides (TMPs) have attracted much attention due to their high Faraday efficiency, good catalytic activity and environmental friendliness. However, the poor performance of TMPs with a single metal component and insufficient structural characteristics have limited the development of TMPs. Metal-organic framework (MOF) materials have received extensive attention in the field of electrocatalysis due to their high specific surface area, large pore size, designable and adjustable pore structure and functionalization. However, most MOFs have low conductivity and it is difficult to achieve good catalytic performance in electrocatalytic water splitting to produce hydrogen. Summary of the invention

[0005] In view of this, the present invention provides an electrocatalyst and a preparation method and application thereof, the main purpose of which is to solve the technical problems of low electrocatalyst activity and poor electrocatalytic performance.

[0006] In one aspect, the present invention provides an electrocatalyst, the electrocatalyst comprising a conductive substrate and an active component; the active component is supported on the surface of the conductive substrate;

[0007] The structural formula of the active ingredient is CeFe-LDH@F-NiCoP;

[0008] Wherein, the F-NiCoP is fluorine-doped nickel cobalt phosphide, and the CeFe-LDH is cerium-iron layered double hydroxide;

[0009] The F-NiCoP in the active component grows in situ on the surface of the conductive substrate in the form of a two-dimensional nanosheet array, and the CeFe-LDH nanoparticles in the active component grow on the surface of the F-NiCoP two-dimensional nanosheet to form a three-dimensional heterogeneous structure of the active component.

[0010] Optionally, the conductive substrate includes a nickel substrate, a nickel-iron substrate, an iron substrate or a stainless steel substrate.

[0011] In a second aspect, the present invention provides a method for preparing the above-mentioned electrocatalyst, the preparation method comprising the following steps:

[0012] S1: Obtaining conductive substrate-loaded NiCo metal-organic framework nanosheet precursor;

[0013] S2: the conductive substrate-supported nickel-cobalt metal-organic framework nanosheet precursor in step S1 is phosphated by calcination to obtain conductive substrate-supported fluorine-doped nickel-cobalt phosphide nanosheets, denoted as F-NiCoP;

[0014] S3: Depositing a cerium source and an iron source on the surface of the fluorine-doped nickel cobalt phosphide nanosheets supported by the conductive substrate in step S2 by electrodeposition to obtain cerium-iron layered double hydroxide, thereby forming an electrocatalyst having a three-dimensional heterostructure of active components, which is recorded as CeFe-LDH@F-NiCoP.

[0015] Optionally, in step S1, the preparation method of the conductive substrate loaded nickel-cobalt metal-organic framework nanosheet precursor includes: heating a raw material containing a cobalt source, a nickel source, an organic ligand and a solvent and a conductive substrate under closed conditions to react I to obtain a nickel-cobalt metal-organic framework nanosheet precursor grown on the conductive substrate.

[0016] Optionally, in step S1, the temperature of the heating reaction I is 100-120° C., and the time of the heating reaction I is 4-10 h.

[0017] Optionally, the temperature of the heating reaction I is selected from any value of 100°C, 103°C, 105°C, 108°C, 110°C, 112°C, 115°C, 118°C, 120°C, or a range between any two thereof; the reaction time I is any value of 4, 5, 6, 7, 8, 9, 10h, or a range between any two thereof.

[0018] Optionally, in step S1, the molar ratio of the cobalt source, the nickel source and the organic ligand is 0.15-0.45:0.15-0.45:0.1-0.3.

[0019] Optionally, in step S1, the cobalt source is selected from cobalt nitrate, cobalt acetate or cobalt chloride; the nickel source is selected from nickel nitrate, nickel acetate or nickel chloride; the organic ligand is selected from terephthalic acid and / or tetrafluoroterephthalic acid; and the solvent comprises a mixed solution of N,N-dimethylformamide, ethanol and deionized water.

[0020] Optionally, the cobalt nitrate is cobalt nitrate hexahydrate, and the nickel nitrate is nickel nitrate hexahydrate.

[0021] Optionally, the heating reaction I is a solvent thermal reaction; the solvent thermal reaction is carried out in a reactor; the product after the heating reaction I is washed with an organic solvent and vacuum dried to obtain a nickel-cobalt metal-organic framework nanosheet precursor grown on a conductive substrate.

[0022] Optionally, in step S2, the method for preparing the conductive substrate-loaded fluorine-doped nickel cobalt phosphide nanosheets includes: heating the conductive substrate-loaded nickel cobalt metal-organic framework nanosheet precursor and phosphate in an inert atmosphere to react II to obtain conductive substrate-loaded fluorine-doped nickel cobalt phosphide nanosheets F-NiCoP.

[0023] Optionally, in step S2, the temperature of the heating reaction II is 350-450° C., and the time of the heating reaction II is 1.5-2.5 h.

[0024] Optionally, the temperature of the heating reaction II is selected from any value among 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, or any range between two thereof; the time of the reaction II is selected from any value among 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5h, or any range between two thereof.

[0025] The conductive substrate in the present invention carries a nickel-cobalt metal-organic framework nanosheet precursor for complete phosphating.

[0026] Optionally, in step S2, the phosphate is selected from sodium hypophosphite.

[0027] Optionally, the sodium hypophosphite is sodium hypophosphite monohydrate; the purity of Ar is 99.99999%; the phosphating temperature is 400°C, and the heating rate is 2°C min -1 , the insulation time is 2h.

[0028] Optionally, the heating reaction II is a phosphating reaction, and the phosphating reaction is carried out in a tubular furnace.

[0029] Optionally, the inert atmosphere comprises an argon atmosphere.

[0030] Optionally, in step S3, the electrodeposition process includes: using a mixed solution of a cerium source and an iron source as an electrolyte, using the conductive substrate-loaded fluorine-doped nickel cobalt phosphide nanosheets in step S2 as a working electrode, using a carbon rod as a counter electrode, and using silver / silver chloride as a reference electrode, performing electrodeposition under constant voltage conditions, and depositing cerium-iron layered double hydroxide on the surface of the conductive substrate-loaded fluorine-doped nickel cobalt phosphide nanosheets.

[0031] Optionally, in step S3, the molar ratio of the cerium source to the iron source is 0.4-1.0:0.6-1.0.

[0032] In the present invention, the amounts of the cerium source and the iron source deposited on the fluorine-doped nickel cobalt phosphide nanosheets loaded on the conductive substrate can be controlled by the deposition time.

[0033] Optionally, the molar ratio of the cerium source to the iron source is selected from 0.5-1.0:0.6-1.0.

[0034] Optionally, the molar ratio of the cerium source to the iron source is selected from 0.5-0.8:0.6-0.8.

[0035] Optionally, in step S3, the molar concentration of the electrolyte is 1-2 mmol / L, the temperature of the electrodeposition is 20-30° C., the voltage of the electrodeposition is -0.8-1.5 V vs. Ag / AgCl, and the time of the electrodeposition is 200-400 s.

[0036] Optionally, the deposition time is any value among 200, 250, 300, 350, 400 s or a range value between any two of them.

[0037] Optionally, in step S3, the electrocatalyst is vacuum dried at a temperature of 60 to 100° C. and for a time of 6 to 12 hours.

[0038] The present invention provides a specific method for preparing a three-dimensional heterogeneous structure electrocatalyst for alkaline large current oxygen evolution, comprising the following steps:

[0039] (1) Weighing cobalt nitrate hexahydrate, nickel nitrate hexahydrate, terephthalic acid and tetrafluoroterephthalic acid, adding them to a mixed solution of N,N-dimethylformamide, ethanol and deionized water, and fully sonicating to obtain a precursor solution after complete dissolution;

[0040] (2) placing nickel foam in the solution prepared in step (1) and subjecting it to sufficient ultrasonic treatment;

[0041] (3) transferring the solution and nickel foam obtained in step (2) into a reaction kettle, sealing it, reacting it at 100-120° C. for 4-10 hours, cooling it naturally to room temperature after the reaction, washing it with N,N-dimethylformamide and methanol, and vacuum drying it to obtain a nickel-cobalt metal-organic framework nanosheet precursor grown on nickel foam;

[0042] (4) placing the nickel-cobalt metal-organic framework precursor and sodium hypophosphite obtained in step (3) into porcelain boats respectively, placing them downstream and upstream of the quartz tube in a tube furnace respectively, heating them to the phosphating reaction temperature under an Ar atmosphere and then keeping them warm for phosphating to obtain fluorine-doped nickel-cobalt phosphide nanosheets (F-NiCoP);

[0043] (5) dissolving cerium nitrate hexahydrate and ferric nitrate nonahydrate in deionized water, and subjecting the mixture to ultrasonic treatment to obtain an electrodeposition solution. The F-NiCoP obtained in step (4) is immersed in the prepared electrodeposition solution, and electrodeposited for a certain period of time under constant voltage conditions. The obtained product is washed with deionized water, and vacuum dried to obtain a three-dimensional heterostructure electrocatalyst of F-NiCoP loaded with cerium iron layered double hydroxide (CeFe-LDH@F-NiCoP).

[0044] The three-dimensional heterogeneous structure electrocatalyst for alkaline large current oxygen evolution provided by the present invention uses nickel foam as a base material, and uses a solvent thermal method to synthesize a nickel-cobalt metal-organic framework nanosheet precursor with nickel and cobalt as metal centers and terephthalic acid and tetrafluoroterephthalic acid as organic ligands, and then phosphates the precursor in a tubular furnace to obtain fluorine-doped nickel-cobalt phosphide nanosheets, and finally uses a three-electrode electrochemical workstation, uses ferric nitrate nonahydrate and cerium nitrate hexahydrate as electrolytes, fluorine-doped nickel-cobalt phosphide nanosheets as working electrodes, carbon rods as counter electrodes, and silver / silver chloride as reference electrodes to electrodeposit cerium-iron layered double hydroxides to obtain the three-dimensional heterogeneous structure electrocatalyst.

[0045] In a third aspect, the present invention provides an electrode material, wherein the electrode material comprises the above-mentioned electrocatalyst.

[0046] In a fourth aspect, the present invention provides the use of the above electrocatalyst in alkaline high current electrocatalytic oxygen evolution.

[0047] The invention provides a design concept for a highly active alkaline, high-current oxygen evolution electrocatalyst. The prepared three-dimensional heterostructure electrocatalyst has abundant catalytic active sites and outstanding oxygen evolution catalytic activity, and exhibits excellent durability under alkaline, high-current conditions, which is of great significance for promoting the development of green and clean energy.

[0048] In a fifth aspect, the present invention provides a standard three-electrode system, with the above-mentioned electrocatalytic material CeFe-LDH@F-NiCoP as the working electrode, Hg / HgO as the reference electrode, and a carbon rod as the counter electrode.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] (1) The present invention provides a three-dimensional heterogeneous structure electrocatalyst (CeFe-LDH@F-NiCoP) in situ grown on the surface of nickel foam for alkaline large current oxygen evolution and a preparation method thereof.

[0051] (2) The nickel foam provided by the present invention has a three-dimensional porous structure and excellent electrical conductivity. It can be used as a base material to prepare an electrocatalyst and can be directly used as a working electrode, effectively improving the catalytic activity and stability of the material.

[0052] (3) The F-NiCoP provided by the present invention is in situ grown on the surface of nickel foam in the form of a two-dimensional nanosheet array, and combined with the surface electrodeposited CeFe-LDH, it can expose abundant catalytic active sites, fully contact with the electrolyte, reduce the internal resistance of the electrocatalyst, and ensure the high catalytic activity and stability of the electrocatalyst.

[0053] (4) The preparation method provided by the present invention is simple, easy to operate, low-cost, and highly controllable, which is conducive to large-scale production and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 This is a flow chart of the preparation of CeFe-LDH@F-NiCoP prepared in Example 1 of the present invention;

[0055] Figure 2 This is a scanning electron microscope image of CeFe-LDH@F-NiCoP prepared in Example 1 of the present invention;

[0056] Figure 3 This is a linear sweep voltammetry curve of electrocatalytic oxygen evolution of CeFe-LDH@F-NiCoP prepared in Example 1 of the present invention, and the electrolyte is a 1.0M KOH aqueous solution;

[0057] Figure 4 This is a Tafel slope curve of CeFe-LDH@F-NiCoP prepared in Example 1 of the present invention;

[0058] Figure 5 CeFe-LDH@F-NiCoP prepared in Example 1 of the present invention is 1Acm -2 Stability test diagram under current density. DETAILED DESCRIPTION

[0059] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.

[0060] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.

[0061] Unless otherwise specified, the analysis methods in the examples all adopt conventional settings and conventional analysis methods of instruments or equipment.

[0062] The analysis method in the embodiment of the present invention is as follows:

[0063] The scanning electron microscope image testing method is: using a scanning electron microscope (model: Quanta 200F) to test the sample.

[0064] The test method for electrocatalytic oxygen evolution is: using an electrochemical workstation (model: CHI1140D) to perform sample testing.

[0065] In the present invention, mM means mmol / L.

[0066] Example 1

[0067] The present invention is as follows Figure 1 The method shown is to prepare a three-dimensional heterostructure electrocatalyst (CeFe-LDH@F-NiCoP), and the steps are as follows:

[0068] (1) 87.3 mg of cobalt nitrate hexahydrate, 29.1 mg of nickel nitrate hexahydrate, 58.1 mg of terephthalic acid and 11.9 mg of tetrafluoroterephthalic acid were added to a mixed solution of 10 mL of N,N-dimethylformamide, 2 mL of ethanol and 1 mL of deionized water, and the mixture was thoroughly sonicated for 20 min. The mixture was then transferred to a 20 mL polytetrafluoroethylene reactor and the treated nickel foam was added. The mixture was subjected to solvent thermal reaction at 120 °C for 6 h. After the reactor was naturally cooled to room temperature, it was washed with N,N-dimethylformamide and methanol, and vacuum dried to obtain a nickel-cobalt metal-organic framework nanosheet precursor (F-NiCo-MOF).

[0069] (2) The F-NiCo-MOF and sodium hypophosphite obtained in step (1) were placed in porcelain boats, respectively, and placed downstream and upstream of the quartz tube in a tube furnace. Then, the mixture was heated at 2 °C min under an Ar atmosphere. -1The tube furnace was heated to 400 °C at a heating rate of 1.5 and kept at this temperature for 2 h to obtain F-NiCo-MOF-derived F-NiCoP nanosheets.

[0070] (3) Using the F-NiCoP nanosheets obtained in step (2) as the working electrode, an electrodeposition solution containing 0.6 mM ferric nitrate nonahydrate and 0.5 mM cerium nitrate hexahydrate, Ag / AgCl as the reference electrode, a carbon rod as the counter electrode, an electrodeposition temperature of 25°C, a constant potential condition voltage of -1.0 V vs. Ag / AgCl, and an electrodeposition time of 300 s, a three-dimensional heterostructure electrocatalyst (CeFe-LDH@F-NiCoP) was prepared.

[0071] Depend on Figure 2 It can be seen that the F-NiCoP two-dimensional nanosheets are neatly grown on the nickel foam substrate material with uniform size and good dispersion, and many CeFe-LDH nanoparticles are also grown on the surface of the two-dimensional nanosheets, indicating the successful formation of the heterogeneous structure.

[0072] The electrocatalytic oxygen evolution performance of the three-dimensional heterogeneous structure electrocatalyst CeFe-LDH@F-NiCoP prepared in Example 1 was tested using a 1.0M KOH aqueous solution. The test process is as follows:

[0073] Shanghai Chenhua CHI1140D workstation was used to conduct the standard three-electrode system, with CeFe-LDH@F-NiCoP as the working electrode, Hg / HgO as the reference electrode, and carbon rod as the counter electrode. The potential range was 0.2-1.0 V at 5 mV s -1 The linear sweep voltammetry curve of the electrocatalyst was tested at a scan rate of 1000 mA cm-1, and the corresponding Tafel slope curve was obtained through the linear sweep voltammetry curve. In addition, the current density of CeFe-LDH@F-NiCoP was set at a constant 1000 mA cm-1. -2 , and record the change of its potential during catalytic oxygen evolution, so as to judge the stability of CeFe-LDH@F-NiCoP in the process of electrocatalytic oxygen evolution.

[0074] Test results such as Figure 3 , 4 and 5; Figure 3 The linear sweep voltammograms of CeFe-LDH@F-NiCoP in alkaline solution are shown at 500 and 1000 mA cm -2 The overpotentials of CeFe-LDH@F-NiCoP at different current densities are as low as 271 and 302 mV, respectively.

[0075] Figure 4 The corresponding Tafel slope curve of CeFe-LDH@F-NiCoP is shown, and its value is 90.8mV dec.-1 , indicating that it has good reaction kinetics.

[0076] Figure 5 It shows that CeFe-LDH@F-NiCoP has excellent long-term stability under 90h working conditions.

[0077] Example 2

[0078] This embodiment follows Figure 1 The method shown is to prepare a three-dimensional heterostructure electrocatalyst (CeFe-LDH@F-NiCoP), and the steps are as follows:

[0079] (1) 101.9 mg of cobalt nitrate hexahydrate, 14.5 mg of nickel nitrate hexahydrate, 49.8 mg of terephthalic acid and 20.8 mg of tetrafluoroterephthalic acid were added to a mixed solution of 10 mL of N,N-dimethylformamide, 2 mL of ethanol and 1 mL of deionized water, and the mixture was fully ultrasonicated for 20 min. The mixture was then transferred to a 20 mL polytetrafluoroethylene reactor and the treated nickel foam was added. The mixture was solvothermally reacted at 120 °C for 6 h. After the reactor was naturally cooled to room temperature, it was washed with N,N-dimethylformamide and methanol, and vacuum dried to obtain a nickel-cobalt metal-organic framework nanosheet precursor (F-NiCo-MOF).

[0080] (2) The F-NiCo-MOF and sodium hypophosphite obtained in step (1) were placed in porcelain boats, respectively, and placed downstream and upstream of the quartz tube in a tube furnace. Then, the mixture was heated at 2 °C min under an Ar atmosphere. -1 The tube furnace was heated to 400 °C at a heating rate of 1.5 and kept at this temperature for 2 h to obtain F-NiCo-MOF-derived F-NiCoP nanosheets.

[0081] (3) The F-NiCoP nanosheets obtained in step (2) were used as the working electrode, 0.5 mM ferric nitrate nonahydrate and 0.6 mM cerium nitrate hexahydrate were used as the electrodeposition solution, Ag / AgCl was used as the reference electrode, the carbon rod was used as the counter electrode, the electrodeposition temperature was 25°C, the constant potential condition voltage was -1.2 V vs. Ag / AgCl, and the electrodeposition time was 240 s to prepare a three-dimensional heterostructure electrocatalyst (CeFe-LDH@F-NiCoP).

[0082] The electrocatalytic oxygen evolution performance test method is the same as that in Example 1.

[0083] Example 3

[0084] This embodiment follows Figure 1 The method shown is to prepare a three-dimensional heterostructure electrocatalyst (CeFe-LDH@F-NiCoP), and the steps are as follows:

[0085] (1) 58.2 mg of cobalt nitrate hexahydrate, 58.2 mg of nickel nitrate hexahydrate, 33.2 mg of terephthalic acid and 41.6 mg of tetrafluoroterephthalic acid were added to a mixed solution of 10 mL of N,N-dimethylformamide, 2 mL of ethanol and 1 mL of deionized water, and the mixture was thoroughly sonicated for 20 min. The mixture was then transferred to a 20 mL polytetrafluoroethylene reactor and the treated nickel foam was added. The mixture was solvothermally reacted at 120 °C for 6 h. After the reactor was naturally cooled to room temperature, the mixture was washed with N,N-dimethylformamide and methanol, and vacuum dried to obtain a nickel-cobalt metal-organic framework nanosheet precursor (F-NiCo-MOF).

[0086] (2) The F-NiCo-MOF and sodium hypophosphite obtained in step (1) were placed in porcelain boats, respectively, and placed downstream and upstream of the quartz tube in a tube furnace. Then, the mixture was heated at 2 °C min under an Ar atmosphere. -1 The tube furnace was heated to 400 °C at a heating rate of 1.5 and kept at this temperature for 2 h to obtain F-NiCo-MOF-derived F-NiCoP nanosheets.

[0087] (3) Using the F-NiCoP nanosheets obtained in step (2) as the working electrode, an electrodeposition solution containing 0.4 mM ferric nitrate nonahydrate and 0.7 mM cerium nitrate hexahydrate, Ag / AgCl as the reference electrode, a carbon rod as the counter electrode, an electrodeposition temperature of 25°C, a constant potential condition voltage of -0.9 V vs. Ag / AgCl, and an electrodeposition time of 360 s, a three-dimensional heterostructure electrocatalyst (CeFe-LDH@F-NiCoP) was prepared.

[0088] The electrocatalytic oxygen evolution performance test method is the same as that in Example 1.

[0089] Example 4

[0090] This embodiment follows Figure 1 The method shown is to prepare a three-dimensional heterostructure electrocatalyst (CeFe-LDH@F-NiCoP), and the steps are as follows:

[0091] (1) 77.6 mg of cobalt nitrate hexahydrate, 38.8 mg of nickel nitrate hexahydrate, 41.5 mg of terephthalic acid and 31.2 mg of tetrafluoroterephthalic acid were added to a mixed solution of 10 mL of N,N-dimethylformamide, 2 mL of ethanol and 1 mL of deionized water, and the mixture was thoroughly sonicated for 20 min. The mixture was then transferred to a 20 mL polytetrafluoroethylene reactor and the treated nickel foam was added. The mixture was solvothermally reacted at 120 °C for 6 h. After the reactor was naturally cooled to room temperature, the mixture was washed with N,N-dimethylformamide and methanol, and vacuum dried to obtain a nickel-cobalt metal-organic framework nanosheet precursor (F-NiCo-MOF).

[0092] (2) The F-NiCo-MOF and sodium hypophosphite obtained in step (1) were placed in porcelain boats, respectively, and placed downstream and upstream of the quartz tube in a tube furnace. Then, the mixture was heated at 2 °C min under an Ar atmosphere. -1 The tube furnace was heated to 400 °C at a heating rate of 1.5 and kept at this temperature for 2 h to obtain F-NiCo-MOF-derived F-NiCoP nanosheets.

[0093] (3) Using the F-NiCoP nanosheets obtained in step (2) as the working electrode, an electrodeposition solution containing 0.8 mM ferric nitrate nonahydrate and 0.4 mM cerium nitrate hexahydrate, Ag / AgCl as the reference electrode, a carbon rod as the counter electrode, an electrodeposition temperature of 25°C, a constant potential condition voltage of -0.9 V vs. Ag / AgCl, and an electrodeposition time of 360 s, a three-dimensional heterostructure electrocatalyst (CeFe-LDH@F-NiCoP) was prepared.

[0094] The electrocatalytic oxygen evolution performance test method is the same as that in Example 1.

[0095] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. An electrocatalyst, characterized in that The electrocatalyst comprises a conductive substrate and an active component; the active component is loaded on the surface of the conductive substrate; The structural formula of the active ingredient is CeFe-LDH@F-NiCoP; Wherein, the F-NiCoP is fluorine-doped nickel cobalt phosphide, and the CeFe-LDH is cerium-iron layered double hydroxide; The F-NiCoP in the active component grows in situ on the surface of the conductive substrate in the form of a two-dimensional nanosheet array, and the CeFe-LDH nanoparticles in the active component grow on the surface of the F-NiCoP two-dimensional nanosheet to form a three-dimensional heterogeneous structure of the active component.

2. An electrocatalyst according to claim 1, characterized in that: The conductive substrate includes a nickel substrate, a nickel-iron substrate, an iron substrate or a stainless steel substrate.

3. The method for preparing an electrocatalyst according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: S1: Obtaining conductive substrate-loaded NiCo metal-organic framework nanosheet precursor; S2: the conductive substrate-supported nickel-cobalt metal-organic framework nanosheet precursor in step S1 is phosphated by calcination to obtain conductive substrate-supported fluorine-doped nickel-cobalt phosphide nanosheets, denoted as F-NiCoP; S3: Depositing a cerium source and an iron source on the surface of the fluorine-doped nickel cobalt phosphide nanosheets supported by the conductive substrate in step S2 by electrodeposition to obtain cerium-iron layered double hydroxide, thereby forming an electrocatalyst having a three-dimensional heterostructure of active components, which is recorded as CeFe-LDH@F-NiCoP.

4. The method for preparing an electrocatalyst according to claim 3, characterized in that: In step S1, the preparation method of the conductive substrate-loaded nickel-cobalt metal-organic framework nanosheet precursor includes: heating a raw material containing a cobalt source, a nickel source, an organic ligand and a solvent and a conductive substrate under closed conditions to react I to obtain a nickel-cobalt metal-organic framework nanosheet precursor grown on a conductive substrate.

5. The method for preparing an electrocatalyst according to claim 4, characterized in that: In step S1, the temperature of the heating reaction I is 100-120° C., and the time of the heating reaction I is 4-10 hours; Preferably, in step S1, the molar ratio of the cobalt source, the nickel source, and the organic ligand is 0.15-0.45:0.15-0.45:0.1-0.3; Preferably, in step S1, the cobalt source is selected from cobalt nitrate, cobalt acetate or cobalt chloride; the nickel source is selected from nickel nitrate, nickel acetate or nickel chloride; the organic ligand is selected from terephthalic acid and / or tetrafluoroterephthalic acid; and the solvent comprises a mixed solution of N,N-dimethylformamide, ethanol and deionized water.

6. The method for preparing an electrocatalyst according to claim 3, characterized in that: In step S2, the preparation method of the conductive substrate-supported fluorine-doped nickel cobalt phosphide nanosheets comprises: heating the conductive substrate-supported nickel cobalt metal-organic framework nanosheet precursor and phosphate in an inert atmosphere to perform reaction II to obtain conductive substrate-supported fluorine-doped nickel cobalt phosphide nanosheets F-NiCoP; Preferably, in step S2, the temperature of the heating reaction II is 350-450° C., and the time of the heating reaction II is 1.5-2.5 h; Preferably, in step S2, the phosphate is selected from sodium hypophosphite.

7. The method for preparing an electrocatalyst according to claim 3, characterized in that: In step S3, the electrodeposition process includes: using a mixed solution of a cerium source and an iron source as an electrolyte, using the conductive substrate-loaded fluorine-doped nickel cobalt phosphide nanosheets in step S2 as a working electrode, using a carbon rod as a counter electrode, and using silver / silver chloride as a reference electrode, performing electrodeposition under constant voltage conditions, and depositing cerium-iron layered double hydroxide on the surface of the conductive substrate-loaded fluorine-doped nickel cobalt phosphide nanosheets.

8. The method for preparing an electrocatalyst according to claim 3, characterized in that: In step S3, the molar ratio of the cerium source to the iron source is 0.4-1.0:0.6-1.0; Preferably, in step S3, the molar concentration of the electrolyte is 1-2 mmol / L, the temperature of the electrodeposition is 20-30° C., the voltage of the electrodeposition is -0.8-1.5 V vs. Ag / AgCl, and the time of the electrodeposition is 200-400 s; Preferably, in step S3, the electrocatalyst is vacuum dried at a temperature of 60 to 100° C. and for a time of 6 to 12 hours.

9. An electrode material, characterized in that: The electrode material comprises an electrocatalyst as claimed in claim 1 or 2.

10. Use of an electrocatalyst as claimed in claim 1 or 2 in alkaline high current electrocatalytic oxygen evolution.

Citation Information

Patent Citations

  • NiFeP bifunctional transition metal phosphide catalyst as well as preparation and use thereof

    CN107376958A

  • NiCoP / NiCo-DHatNF composite material, and preparation method and application thereof

    CN112156798A

  • Three-dimensional multi-stage MOF (Metal Organic Framework) derived phosphorus-cobalt-iron / nickel-cobalt layered double hydroxide / nickel foam core-shell composite electrode of supercapacitor

    CN116598148A